The importance of aerobic fitness for tennis: a review (part 1) - Genevois, C. (Coaching and Sport Science Review, 2019)
Tennis is an intermittent sport involving different physical components, one of which is aerobic fitness. Scientific research has provided information about the physiological demands of tennis competition and some specific protocols have been developed to combine aerobic testing with technical efficiency testing and training. This paper will provide a rationale behind aerobic fitness training for tennis players.